IMPROVING THE COMMODITY POLICY OF LOCAL INDUSTRIAL ENTERPRISES - Boyjigitov Sanjarbek Komiljo o’g’li (International Journal of Innovations in Engineering Research and Technology, 2021)
The article describes the role of commodity policy and assortment in local industrial enterprises, the role of identifying low-profit goods in the range and optimizing production costs by improving commodity policy. The strategic directions of the commodity policy of local industrial enterprises were discussed.